UJI PUPUK KCL DAN BOKASI GULMA TERHADAP PRODUKSI TANAMAN JAGUNG MANIS (Zea mays saccarata Sturt) - Zulkifli Zulkifli; Putri Lukmana Sari (UIR Press, 2018)
Corn is the most important food commodity which contains second-grade carbohydrate after rice. People's concern over agriculture and the environment in the last years has been increasing, as it hurts the environment because of the use of inorganic materials to increase agricultural production. To minimize the negative impact, organic farming is natural agriculture that can reduce the use of inorganic materials. Bokashi is a fermented organic fertilizer with EM4 technology (Effective Microorganisms-4). KCL fertilizer is an organic fertilizer to play a role in strengthening the plant so as not to be easily broken. The objective of this research is to make the experiment with the effect of giving KCL and weed bokashi interaction and single to the production of sweet corn. This study used Completely Randomized Design (RAL), Factorial 4x4 with treatment as a Dose of KCL consisting of 4 levels; K0. Without the Giving of KCL, K1 KCL 20 g/plot, K2 KCL 40 g/ plot, K3 KCL 60 g/plot and Dose weed bokashi consisted of 4 levels; B0 Without the giving of weed bokashi, B1 weed bokashi 480 g/plot, B2 weed bokashi 960g/plot, B3 weed bokashi 1.440g/plot. Parameters observed include; cob length, convoluted cob and weight cob of sweet corn. The results of this study showed that KCL and weed bokashi fertilizer experiment to production sweet corn interaction had an effect on cob length, convoluted cob and weight cob of sweet corn, which doses of KCl will reduce the application of fertilizer Bokashi and vice versa, and KCL. Weed bokashi were balanced to maximize the production of sweet corn that is present in KCL 60 g/plot and Bokash weed bokashi 480 g/plot and KCL 20 g/plot and weed bokashi 960g/plot with cob length 30,00 cm, convoluted cob 20,17 cm and weight cob 465,00 g per cob.